2002
DOI: 10.1128/jvi.76.6.2871-2880.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Temperature-Sensitive Mutations in the Phosphoprotein of Respiratory Syncytial Virus That Are Likely Involved in Its Interaction with the Nucleoprotein

Abstract: The phosphoprotein (P) of human respiratory syncytial virus (RSV) is an essential component of the viral RNA polymerase, along with the large polymerase (L), nucleocapsid (N), and M2-1 proteins. By screening a randomly mutagenized P gene cDNA library, two independent mutations, one with a substitution of glycine at position 172 by serine (G172S) and the other with a substitution of glutamic acid at position 176 by glycine (E176G), were identified to result in the loss of N-P interaction at 37°C in the yeast tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
(41 reference statements)
5
17
0
Order By: Relevance
“…Recently, we and the other groups have reported that other regions in P protein are also involved in its interaction with N protein (20,22). This report also demonstrated that phosphorylation of RSV P protein was important for N-P protein interaction.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Recently, we and the other groups have reported that other regions in P protein are also involved in its interaction with N protein (20,22). This report also demonstrated that phosphorylation of RSV P protein was important for N-P protein interaction.…”
Section: Discussionsupporting
confidence: 67%
“…The plasmids expressing RSV N, P, and L proteins under the control of the T7 promoter (in the pCITE vector) were described previously (18). The RSV minigenome, pRSVCAT, encodes a negative-sense chloramphenicol acetyltransferase (CAT) gene under the control of the T7 promoter (22). pRSVCAT/EGFP was constructed by inserting an enhanced green fluorescent protein (EGFP) gene, which was flanked by the RSV gene start and gene end sequence downstream of the CAT gene, into pRSVCAT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SH 0 is the 7.5 kDa non-glycosylated form and is the most common form expressed. SH g is the N-linked glycosylated form (15)(16)(17)(18)(19) kDa) which is a precursor to SH p ; the latter (21-40 kDa) is a polylactosaminoglycan modified form of the protein. SH t is a truncated, 4.8 kDa protein generated by translation initiation at in internal AUG [45].…”
Section: Sh (Small Hydrophobic) Glycoproteinmentioning
confidence: 99%
“…The C-terminus of P is required for interaction with N [17]. Yeast two-hybrid analysis shows that the C-terminus of P is important in forming heterodimers with N [18], with changes in two residues in this region of P (E176 and G172) resulting in a temperature-sensitive phenotype due to reduced interaction with N [19]. Phosphorylation of P has been shown to be dispensable for most of its assembly functions, e.g., P-P, P-N and P-M2-1 interactions in cell-free and cell culture systems [20,21].…”
Section: A Formation Of Cytoplasmic Inclusionsmentioning
confidence: 99%